A Study of Risk Communication and Perceptions of Official and Public Agendas in the Context of Emergencies: Based on the Itaewon Stampede - Yanchun Chen; Gaogao Peng; Yuwei Tu; Tianzhi Ren (SAGE Open)
On October 29, 2022, a large-scale stampede occurred in Seoul, South Korea, which caused worldwide shock and garnered global attention and discussion. In this article, a study on the thematic characteristics of social media platforms during major sudden risk events is carried out utilizing online agenda setting. Furthermore, the consensus and divergence between the official and public agendas in risk communication are analyzed to understand their interactive relationship. The study reveals that the risk communication of the stampede comprises seven core issues across three stages, including risk information, warnings, preparedness, uncertainty reduction, utility, assurance, and public risk perception. These findings offer insights for media coverage to focus on critical aspects, assist the government in conducting effective administration and risk communication, and provide empirical evidence for the agenda-setting in the field of sudden safety accidents within the online realm, aiming to complement current academic research.